Microwave carbon thermal shock controllable preparation and application of metal monatomic / nanocluster co-doped short carbon fiber

Co-doping of metal single atoms/nano clusters on the surface of chopped carbon fibers through microwave carbon thermal shock reduction, solving the problems of fiber inertia and side reactions in traditional processes, and improving the electromagnetic wave absorption performance of composite materials.

CN119686100AActive Publication Date: 2025-03-25ZHONGBEI UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411924831.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

In the traditional metal atom doped chopped fiber preparation process, the inertia of the fiber will hinder the surface load of metal particles, and there are inevitable side reactions during the synthesis process, resulting in the limitation of composite materials in practical applications.

Method used

The microwave carbon thermal shock reduction method is adopted to simultaneously complete the activated oxygen-containing functional group etching of the activated oxygen-containing functional group on the surface of the carbon fiber by pretreating the defects generated on the surface of the chopped carbon fiber and the anchoring effect of the active oxygen-containing functional group on the surface of the carbon fiber.

Benefits of technology

The defect manufacturing of inert carbon fiber surfaces is achieved synchronously with the reduction doping of metals, simplifying the process, reducing costs, avoiding the occurrence of side reactions, and improving the electromagnetic wave absorption performance of composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119686100A_ABST
    Figure CN119686100A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of functional carbon fiber composite materials, in particular to microwave carbon thermal shock controllable preparation and application of metal monatomic / nanocluster co-doped chopped carbon fibers, the chopped carbon fibers are dispersed in a cellulose solution and subjected to microwave surface pretreatment, then the chopped carbon fibers are blended with metal salt, and the metal monatomic / nanocluster co-doped chopped carbon fibers are obtained. Metal salt ions are effectively anchored by using oxygen-containing functional groups on the surfaces of the pretreated chopped carbon fibers, and a blending system is placed in a microwave oven for carbon thermal shock, so that the metal ions are reduced into metal monatomic / nanoclusters while defects are generated on the surfaces of the inert carbon fibers. The green, environment-friendly and convenient microwave carbon thermal shock process is adopted, defect introduction on the surface of the inert carbon fiber and simultaneous metal reduction doping can be achieved within several minutes, and the problems of unavoidable side reaction, single carbon fiber electromagnetic wave loss mechanism and the like existing in a traditional preparation method are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional carbon fiber composite materials, and in particular to a microwave carbon thermal shock controllable preparation and application of metal single atom / nano cluster co-doped chopped carbon fibers. Background Art

[0002] Carbon fiber is a fibrous material made of carbon atoms bonded together by strong chemical bonds. It has many advantages, such as light weight, high strength, good mechanical properties and toughness, and environmental friendliness. It has great application potential in aerospace, automobile manufacturing and other fields. In addition, carbon fiber also has excellent dielectric properties. Researchers usually compound it with nano-functional particles to achieve different functions and uses. For example, composite materials formed with ferrites, transition metal nanoparticles, etc. have shown significant advantages in the fields of electromagnetic shielding and electromagnetic wave absorption.

[0003] At present, a variety of preparation methods for metal nanoparticles and chopped carbon fiber composites have been developed, including hydrothermal method, high temperature pyrolysis method, chemical vapor deposition method, microwave carbon thermal shock reduction method, etc. Among them, microwave carbon thermal shock reduction method can significantly improve the surface roughness and increase the specific surface area of ​​the fiber; at the same time, it can also form functional groups on the surface of carbon fibers, improve surface activity and wettability, and realize the simultaneous fiber surface treatment and metal particle reduction modification, which is simple, efficient and environmentally friendly. In addition, the microwave carbon thermal shock reduction method has a short reaction time (within a few minutes) and can effectively inhibit the occurrence of various side reactions. By simply changing the amount of metal salt precursor, scale-controllable metal single atoms and their cluster species can be quickly obtained, which is easy to meet the needs of industrial production. However, at present, there are few reports on the preparation of controllable metal atom-doped chopped fiber absorbers using microwave carbon thermal shock reduction method.

[0004] Introducing metal single atoms and their nanoclusters on the surface of carbon fiber can break the symmetrical carbon hexagonal structure, form dipoles, enhance the dielectric polarization effect, and then synergistically improve the absorption performance of the composite material with the intrinsic dielectric effect of carbon fiber. Therefore, it has broad application prospects in the fields of electromagnetic shielding and electromagnetic wave absorption. Summary of the invention

[0005] In order to solve the problems in the traditional metal atom-doped chopped fiber preparation process that the inertia of the fiber hinders the surface loading of the metal particles, and there are inevitable side reactions in the synthesis process, which result in the prepared composite materials being limited in practical applications, the present invention provides a microwave carbon thermal shock controllable preparation and application of metal single atom / nanocluster co-doped chopped carbon fibers.

[0006] The present invention is realized by the following technical scheme: A microwave carbon thermal shock controllable preparation of metal single atom / nano cluster co-doped chopped carbon fiber comprises the following steps: (1) preparing a cellulose solution, then dispersing chopped carbon fiber powder in the cellulose solution, and ultrasonically dispersing to obtain a chopped carbon fiber dispersion; (2) placing the chopped carbon fiber dispersion in a microwave oven for microwave pretreatment to obtain a surface pretreated chopped carbon fiber dispersion; (3) preparing a metal salt aqueous solution, and then adding it to the surface pretreated chopped carbon fiber dispersion prepared in step (2), and ultrasonically treating it, so as to make the metal ions uniformly loaded on the surface of the chopped carbon fibers by utilizing the defects generated by the surface pretreatment of the chopped carbon fibers and the anchoring effect of the active groups of cellulose on the metal ions, thereby obtaining a metal salt / chopped carbon fiber mixed system; (4) The mixed system obtained in step (3) is placed in a microwave oven for microwave reaction. During this process, the π electron cloud conjugated system of the chopped carbon fiber produces multiple interactions with the microwave field, forming an arc plasma in a limited space, completing the rapid establishment of the local thermal environment of the carbon fiber and causing its surface to be etched by active oxygen-containing functional groups to form surface defects. At the same time, the reduction and doping of metal ions are simultaneously completed to obtain metal single atom / nanocluster co-doped chopped carbon fiber.

[0007] As a further improvement of the preparation technical solution of the present invention, the cellulose is selected from any one of methyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose or a mixture of several of them.

[0008] As a further improvement of the preparation technology scheme of the present invention, in step (1), the ultrasonic power is 200-400 W, and the ultrasonic dispersion time is 10-20 min.

[0009] As a further improvement of the preparation technology scheme of the present invention, in step (1), the mass ratio of the chopped carbon fibers to the cellulose in the chopped carbon fiber dispersion is 2:1.

[0010] As a further improvement of the preparation technology scheme of the present invention, in step (1), the concentration of the cellulose solution is 0.5-1.5 wt %.

[0011] As a further improvement of the preparation technology scheme of the present invention, in step (2), the power of the microwave surface pretreatment is 500-700 W, and the pretreatment time is 2-4 min.

[0012] As a further improvement of the preparation technical scheme of the present invention, in step (3), the metal salt is a mixture of one or more metal salts of transition metals iron, cobalt, and nickel in any proportion, and the concentration of the metal salt aqueous solution is 0.05~0.1mmol / L; the metal salt aqueous solution is added to the surface pretreated chopped carbon fiber dispersion prepared in step (2) according to a mass ratio of chopped carbon fiber: metal ion of 500~1000:20~40.

[0013] As a further improvement of the preparation technology scheme of the present invention, in step (3), the ultrasonic power is 200-400 W, and the ultrasonic time is 10-20 min.

[0014] As a further improvement of the preparation technical solution of the present invention, in step (4), the power of the microwave reaction is 500-700 W, and the reaction time is 3-7 min.

[0015] The present invention also provides the use of the metal single atom / nanocluster co-doped chopped carbon fiber prepared by controllable microwave carbon thermal shock of the metal single atom / nanocluster co-doped chopped carbon fiber in electromagnetic shielding and electromagnetic wave absorption.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention avoids the use of multiple types of chemical reducing agents that must be used in conventional preparation processes. Therefore, the preparation process is more environmentally friendly and the product is purer, effectively solving the problems of significantly increased costs and pollution of the production environment.

[0017] (2) The present invention realizes the simultaneous creation of defects on the surface of inert carbon fibers and reduction doping of metals, has simple steps, is easy to operate, and can effectively save manpower and material resources. Therefore, it is easy to carry out large-scale industrial production.

[0018] (3) The present invention can form atomic-scale electromagnetic energy conversion sites on the surface of carbon fiber, thereby improving the electromagnetic wave absorption performance of carbon fiber, thereby effectively solving the problem of the single wave absorption mechanism of carbon fiber.

[0019] (4) Based on the conductivity of carbon fiber itself, the present invention uses microwave energy to achieve local rapid heating and rapid reaction. It takes only 2 to 6 minutes from the formation of carbon fiber surface defects to the reduction doping of metal atoms, which effectively solves the inevitable side reaction problem of traditional preparation methods. In addition, by simply controlling the ratio of metal salt precursor to chopped carbon fiber, the scale of metal atom dopants can be effectively controlled, that is, the ratio of metal single atoms to nanoclusters and the scale of nanoclusters can be effectively controlled to prepare the performance of carbon fiber composite materials. Therefore, the application potential is huge.

[0020] (5) During the preparation process, the active groups of cellulose effectively anchored the metal ions. In addition, they participated in the microwave carbon reduction process and formed an effective conductive network in the system, which further promoted the uniform response of the system to microwave energy. Almost all of the cellulose decomposed or participated in the reaction in a high-temperature environment. Therefore, there was no cellulose residue in the obtained metal single atom / nanocluster co-doped chopped carbon fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0023] Figure 1 XRD spectra of Fe-doped chopped carbon fibers and pure chopped carbon fibers prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0024] Figure 2 The electrical conductivity of the Fe-doped chopped carbon fibers and pure chopped carbon fibers prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0025] Figure 3 Electromagnetic wave reflection loss (RL) of Fe-doped chopped carbon fibers and pure chopped carbon fibers prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0026] Figure 4 The RL is the Fe-doped chopped carbon fiber prepared in Examples 1 to 3 and Comparative Examples 3 to 5. DETAILED DESCRIPTION

[0027] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0029] The present invention provides a specific embodiment of the microwave carbon thermal shock controllable preparation of metal single atom / nano cluster co-doped chopped carbon fibers, comprising the following steps: (1) preparing a cellulose solution, then dispersing chopped carbon fiber powder in the cellulose solution, and ultrasonically dispersing to obtain a chopped carbon fiber dispersion; (2) placing the chopped carbon fiber dispersion in a microwave oven for microwave pretreatment to obtain a surface pretreated chopped carbon fiber dispersion; (3) preparing a metal salt aqueous solution, and then adding it to the surface pretreated chopped carbon fiber dispersion prepared in step (2), and ultrasonically treating it, so as to make the metal ions uniformly loaded on the surface of the chopped carbon fibers by utilizing the defects generated by the surface pretreatment of the chopped carbon fibers and the anchoring effect of the active groups of cellulose on the metal ions, thereby obtaining a metal salt / chopped carbon fiber mixed system; (4) The mixed system obtained in step (3) is placed in a microwave oven for microwave reaction. During this process, the π electron cloud conjugated system of the chopped carbon fiber produces multiple interactions with the microwave field, forming an arc plasma in a limited space, completing the rapid establishment of the local thermal environment of the carbon fiber and causing its surface to be etched by active oxygen-containing functional groups to form surface defects. At the same time, the reduction and doping of metal ions are simultaneously completed to obtain metal single atom / nanocluster co-doped chopped carbon fiber.

[0030] In one embodiment provided by the present invention, the cellulose is selected from any one of methyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose, or a mixture of several of them.

[0031] In another embodiment provided by the present invention, in step (1), the ultrasonic power is 200-400 W, and the ultrasonic dispersion time is 10-20 min.

[0032] In one embodiment provided by the present invention, in step (1), the mass ratio of the chopped carbon fibers to the cellulose in the chopped carbon fiber dispersion is 2:1.

[0033] In another embodiment provided by the present invention, in step (1), the concentration of the cellulose solution is 0.5-1.5 wt %.

[0034] In one embodiment provided by the present invention, in step (2), the power of the microwave surface pretreatment is 500-700 W, and the pretreatment time is 2-4 min.

[0035] In another embodiment provided by the present invention, in step (3), the metal salt is a mixture of one or more metal salts of transition metals iron, cobalt, and nickel in any proportion, and the concentration of the metal salt aqueous solution is 0.05~0.1 mmol / L; the metal salt aqueous solution is added to the surface pretreated chopped carbon fiber dispersion prepared in step (2) according to a mass ratio of chopped carbon fiber: metal ion of 500~1000:20~40.

[0036] In one embodiment provided by the present invention, in step (3), the ultrasonic power is 200-400 W, and the ultrasonic time is 10-20 min.

[0037] In another embodiment provided by the present invention, in step (4), the power of the microwave reaction is 500-700 W, and the reaction time is 3-7 min.

[0038] In the present invention, the metal single atom / nanocluster co-doped chopped carbon fiber prepared by microwave carbon thermal shock controllable is used in electromagnetic shielding and electromagnetic wave absorption.

[0039] The specific embodiments of the present invention are described in detail below. The performance testing method adopted by the present invention is as follows:

[0040] X-ray diffraction (XRD): X-ray diffractometer 2700BX (Haoyuan, China) was used for testing.

[0041] Resistivity: A uniform mixture of 20 wt % sample and 80 wt % paraffin was made into a disc with a diameter of 7.00 mm and tested by a four-probe resistivity tester RTS-9 (Four Probes Tech, China).

[0042] Absorption performance: A uniform mixture of 20wt% sample and 80wt% paraffin was made into a coaxial ring with an inner diameter of 3.04mm and an outer diameter of 7.00mm. The dielectric constant and magnetic permeability of the ring were tested in the range of 2-18 GHz using a vector network analyzer 3672C (Ceyear, China) with the coaxial reflection / transmission method. The electromagnetic wave absorption performance RL versus frequency curve (RL-f) in the range of 2-18 GHz was calculated using the transmission line theory.

[0043] The specific embodiments of the present invention are described in detail below. Embodiment 1:

[0044] A microwave carbon thermal shock controllable preparation of Fe single atom / nano cluster co-doped chopped carbon fiber comprises the following steps: (1) A 0.5 wt% hydroxyethyl cellulose (HEC) solution was prepared, and the chopped carbon fiber was dispersed in the solution at a mass ratio of chopped carbon fiber:HEC = 2:1. The solution was ultrasonicated at a power of 400 W for 10 min to obtain a chopped carbon fiber / HEC dispersion.

[0045] (2) The chopped carbon fiber / HEC dispersion was placed in a microwave oven and surface pretreated at a power of 600 W. After 3 minutes, a surface pretreated chopped carbon fiber / HEC dispersion was obtained.

[0046] (3) Add 40 mg of Fe 2 (SO 4 ) 3Add to 1L deionized water, dissolve to obtain 0.1mmol / L Fe salt solution, and then follow the CF:Fe 3+ =1000:40 mass ratio is added to the surface pretreated chopped carbon fiber / HEC dispersion prepared in step (2), and ultrasonicated at 400 W for 10 min. The defects generated after the surface pretreatment of the chopped carbon fiber and the anchoring effect of the active groups of HEC on Fe ions are utilized to uniformly load the Fe ions on the surface of the chopped carbon fiber, thereby obtaining an Fe salt / chopped carbon fiber mixed system.

[0047] (4) The mixed system obtained in step (3) is placed in a microwave oven and subjected to microwave reaction at a power of 700 W for 5 min. During this process, the π electron cloud conjugated system of the chopped carbon fiber produces multiple interactions with the microwave field, forming an arc plasma in a limited space, thereby achieving rapid establishment of a local thermal environment for the chopped carbon fiber and etching its surface with active oxygen-containing functional groups to form surface defects. At the same time, Fe ions are simultaneously reduced to Fe single atoms and nanoclusters and co-doped with the chopped carbon fiber to obtain Fe single atom / nanocluster co-doped chopped carbon fiber.

[0048] Comparative Example 1: The preparation of Fe single atom doped chopped carbon fibers by microwave carbon thermal shock is exactly the same as that in Example 1, except that the concentration of the iron sulfate solution in step (3) is 0.01 mmol / L.

[0049] Comparative Example 2: A microwave carbon thermal shock preparation of Fe nanoclusters doped with chopped carbon fibers is exactly the same as in Example 1, except that the concentration of the iron sulfate solution in step (3) is 1 mmol / L.

[0050] Embodiment 2: The method is exactly the same as Example 1, except that the concentration of the HEC solution in step (1) is 1 wt %, to obtain Fe single atom / nano cluster co-doped chopped carbon fibers.

[0051] Embodiment 3: The method is exactly the same as Example 1, except that the microwave reaction time in step (4) is 7 min, and Fe single atom / nanocluster co-doped chopped carbon fibers are obtained. Comparative Example 3:

[0052] The same as Example 1, except that the surface pretreatment process in step (2) is omitted. Comparative Example 4:

[0053] The same as Example 1, except that the microwave power of the surface pretreatment process in step (2) is 400W. Comparative Example 5:

[0054] The process is exactly the same as in Example 1, except that the microwave treatment time of the surface pretreatment process in step (2) is 6 min.

[0055] Figure 1 The XRD spectra of Fe-doped chopped carbon fibers and pure chopped carbon fibers prepared in Example 1, Comparative Example 1 and Comparative Example 2. According to the PDF card, the two characteristic peaks at 25.1° and 43.3° correspond to the (002) crystal plane and (100) crystal plane of carbon, respectively. In addition to the diffraction peak of carbon, no crystal phase diffraction peak of Fe was detected in Example 1, Comparative Example 1 and Comparative Example 2, indicating that the Fe substances of these materials all have a small size (less than 2nm), which is lower than the detectable range of conventional XRD. Example 1 obtains Fe single atom / nanocluster co-doped chopped carbon fibers, and its performance is also optimal. In Comparative Example 1, a low amount of iron salt was added to obtain metal single atom-doped chopped carbon fibers. In Comparative Example 2, the amount of Fe salt added reached 1 mmol / L, and the high amount of iron salt added resulted in the formation of a composite with nanoclusters (CAs) as doping units on the surface of the chopped carbon fibers. Therefore, it is shown that by accurately controlling the amount of iron salt added (i.e., the mass ratio of iron salt to chopped carbon fibers), the controllable preparation of chopped carbon fibers doped with metal atoms of different scales can be successfully achieved. In addition, during the material preparation process, the active groups of HEC effectively anchored metal ions, participated in the microwave carbon reduction process, and formed an effective conductive network in the system, further promoting the uniform and rapid response of the system to microwave energy. However, in the XRD detection of the sample, there was no characteristic peak indicating HEC (~18.97°), indicating that all HEC was decomposed or participated in the reaction in a high temperature environment. Therefore, there was no HEC residue in the obtained Fe-doped chopped carbon fiber.

[0056] Depend on Figure 2 It can be seen that compared with pure chopped carbon fibers, the electrical conductivity of the metal-doped chopped carbon fiber composite materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 are significantly reduced. This is attributed to the surface defects formed by etching of the carbon fiber surface by active oxygen-containing functional groups during the microwave reaction, the point defects on the carbon fiber surface caused by Fe doping, and the redistribution of surface charges, which are not only beneficial to the improvement of polarization loss electromagnetic wave performance, but also can effectively solve the problem of poor interface impedance matching performance caused by the high electrical conductivity of carbon fibers.

[0057] Depend on Figure 3It can be seen that the maximum effective absorption bandwidth of the Fe single atom / nanocluster co-doped chopped carbon fiber prepared in Example 1 reaches 6.36 GHz, which is significantly improved compared with the 4.64 GHz of the Fe single atom-doped chopped carbon fiber prepared in Comparative Example 1 with the same filling amount and the 4.52 GHz of the Fe nanocluster-doped chopped carbon fiber prepared in Comparative Example 2. At the same time, the Fe single atom / nanocluster co-doped chopped carbon fiber prepared in Example 1 obtained a minimum reflection loss of -51.46 dB, which is also significantly better than that of Comparative Examples 1 and 2. The reason is that: Fe single atoms and Fe nanoclusters, as multi-scale dipoles, form more diverse dipole polarization relaxation paths inside the material, which significantly enhances the polarization loss electromagnetic wave capability. Therefore, the wave absorption performance of Fe single atom / nanocluster co-doped chopped carbon fiber is significantly improved. This is due to the improvement of the traditional preparation process of the present invention, which not only effectively improves the inertness of the carbon fiber surface, but also realizes the fine control of the metal atom doping scale, thereby effectively solving the problem of the single electromagnetic wave loss mechanism of carbon fiber.

[0058] Depend on Figure 4 It can be seen that Example 1, Example 2 and Example 3 respectively obtained minimum reflection losses of -51.46 dB, -45.67 dB and -46.01 dB in the range of 2 to 18 GHz, which are significantly better than those of Comparative Example 3, Comparative Example 4 and Comparative Example 5. At the same time, Example 1 obtained a maximum effective absorption bandwidth of 6.36 GHz, which is better than Comparative Example 3 (3.40 GHz), Comparative Example 4 (3.20 GHz) and Comparative Example 5 (5.14 GHz). It shows that the surface pretreatment process is of great significance for the method of the present invention to obtain Fe single atom / nanocluster co-doped chopped carbon fibers with excellent performance.

[0059] The above is only a specific implementation of the present invention, which enables those skilled in the art to understand or implement the present invention. Although detailed descriptions are given with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments, and they should all be covered by the protection scope of the claims.

Claims

1. A microwave carbon thermal shock controllable preparation of metal single atom / nano cluster co-doped chopped carbon fiber, characterized in that: The following steps are involved: (1) preparing a cellulose solution, then dispersing chopped carbon fiber powder in the cellulose solution, and ultrasonically dispersing to obtain a chopped carbon fiber dispersion; (2) placing the chopped carbon fiber dispersion in a microwave oven for microwave pretreatment to obtain a surface pretreated chopped carbon fiber dispersion; (3) preparing a metal salt aqueous solution, and then adding it to the surface pretreated chopped carbon fiber dispersion prepared in step (2), and ultrasonically treating it, so as to make the metal ions uniformly loaded on the surface of the chopped carbon fibers by utilizing the defects generated by the surface pretreatment of the chopped carbon fibers and the anchoring effect of the active groups of cellulose on the metal ions, thereby obtaining a metal salt / chopped carbon fiber mixed system; (4) The mixed system obtained in step (3) is placed in a microwave oven for microwave reaction. During this process, the π electron cloud conjugated system of the chopped carbon fiber produces multiple interactions with the microwave field, forming an arc plasma in a limited space, completing the rapid establishment of the local thermal environment of the carbon fiber and causing its surface to be etched by active oxygen-containing functional groups to form surface defects. At the same time, the reduction and doping of metal ions are simultaneously completed to obtain metal single atom / nanocluster co-doped chopped carbon fiber.

2. The microwave carbon thermal shock controllable preparation of metal single atom / nanocluster co-doped chopped carbon fiber according to claim 1, characterized in that: The cellulose is selected from any one of methyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose or a mixture of several of them.

3. The microwave carbon thermal shock controllable preparation of metal single atom / nanocluster co-doped chopped carbon fiber according to claim 1, characterized in that: In step (1), the ultrasonic power is 200-400 W, and the ultrasonic dispersion time is 10-20 min.

4. The microwave carbon thermal shock controllable preparation of metal single atom / nanocluster co-doped chopped carbon fiber according to claim 1, characterized in that: In step (1), the mass ratio of the chopped carbon fibers to the cellulose in the chopped carbon fiber dispersion is 2:

1.

5. The microwave carbon thermal shock controllable preparation of metal single atom / nanocluster co-doped chopped carbon fiber according to claim 1, characterized in that: In step (1), the concentration of the cellulose solution is 0.5-1.5 wt%.

6. The microwave carbon thermal shock controllable preparation of metal single atom / nanocluster co-doped chopped carbon fiber according to claim 1, characterized in that: In step (2), the power of the microwave surface pretreatment is 500-700 W, and the pretreatment time is 2-4 min.

7. The microwave carbon thermal shock controllable preparation of metal single atom / nanocluster co-doped chopped carbon fiber according to claim 1, characterized in that: In step (3), the metal salt is a mixture of one or more metal salts of transition metals iron, cobalt, and nickel in any proportion, and the concentration of the metal salt aqueous solution is 0.05~0.1 mmol / L; the metal salt aqueous solution is added to the surface pretreated chopped carbon fiber dispersion prepared in step (2) according to a mass ratio of chopped carbon fiber: metal ion of 500~1000:20~40.

8. The microwave carbon thermal shock controllable preparation of metal single atom / nanocluster co-doped chopped carbon fiber according to claim 1, characterized in that: In step (3), the ultrasonic power is 200-400 W, and the ultrasonic time is 10-20 min.

9. The microwave carbon thermal shock controllable preparation of metal single atom / nanocluster co-doped chopped carbon fiber according to claim 1, characterized in that: In step (4), the power of the microwave reaction is 500-700 W, and the reaction time is 3-7 min.

10. Application of the metal single atom / nanocluster co-doped chopped carbon fiber prepared by microwave carbon thermal shock controllable by the metal single atom / nanocluster co-doped chopped carbon fiber as claimed in any one of claims 1 to 9 in electromagnetic shielding and electromagnetic wave absorption.

Citation Information

Patent Citations

  • Carbon fiber porous layer composite material as well as preparation method and application thereof

    CN116446181A

  • Microwave preparation and application of metal monatomic doped reduced graphene oxide dielectric material

    CN116750754A

  • CF surface modification method and preparation method of electromagnetic wave-absorbing composite material thereof

    CN118461307A

  • Efficient microwave preparation method with one-step simultaneous reduction / embedding and application of metal monatomic-doped reduced graphene oxide dielectric material

    US20240174518A1